Impact of periictal interventions on respiratory dysfunction, postictal EEG suppression, and postictal immobility. (27th September 2012) - Seyal, Masud; Bateman, Lisa M.; Li, Chin‐Shang
Summary Purpose: Sudden unexpected death in epilepsy (SUDEP) is the leading cause of epilepsy‐related mortality. Seizure‐related respiratory dysfunction (RD), the duration of postictal generalized electroencephalography (EEG) suppression (PGES), and duration of postictal immobility (PI) may be important in the pathophysiology of SUDEP. Periictal interventions may reduce the risk of SUDEP. Methods: We assessed the impact of periictal nursing interventions on RD, PGES, and PI duration in patients with localization‐related epilepsy and secondarily generalized convulsions (GCs) recorded during video‐EEG telemetry in the epilepsy monitoring unit. Video‐EEG data were retrospectively reviewed. Interventions including administration of supplemental oxygen, oropharyngeal suction, and patient repositioning were evaluated. Interventions were performed based on nursing clinical judgment at the bedside and were not randomized. The two‐sided Wilcoxon rank‐sum test was used to compare GCs with and those without intervention. Robust simple linear regression was used to assess the association between timing of intervention and duration of hypoxemia (SaO2 < 90%), PGES, and PI using data from only the first GC for each patient. Key Findings: Data from 39 patients with 105 GCs were analyzed. PGES >2 s occurred following 31 GCs in 16 patients. There were 21 GCs with no intervention (NOINT) and 84 GC with interventions (INT). In the INT group, the duration of hypoxemia was shorter (p = 0.0014) when intervention occurred before hypoxemia onset (mean duration 53.1 s) than when intervention was delayed (mean duration 132.42 s). Linear regression indicated that in GCs with nursing interventions, earlier intervention was associated with shorter duration of hypoxemia (p < 0.0001) and shorter duration of PGES (p = 0.0012). Seizure duration (p < 0.0001) and convulsion duration (p = 0.0457) were shorter with earlier intervention. PI duration was longer for GCs with PGES than GCs without PGES (p < 0.0001). The mean delay to first active nonrespiratory movement following GCs with PGES was 251.96 s and for GC without PGES was 66.06 s. The duration of PI was positively associated with lower SaO2 nadir (p = 0.003) and longer duration of oxygen desaturation (p = 0.0026). There was no association between PI duration and seizure duration (p = 0.773), between PI duration and PGES duration (p = 0.758), or between PI duration and the timing of first intervention relative to seizure onset (p = 0.823). PGES did not occur in the NOINT group. The mean duration of desaturation was longer (110.9 vs. 49.9 s) (p < 0.0001), mean SaO2 nadir was lower (72.8% vs. 79.7%) (p = 0.0086), and mean end‐tidal CO2 was higher (58.6 vs. 50.3 mmHg) (p = 0.0359) in the INT group compared with the NOINT group. The duration of the seizure or of the convulsive component was not significantly different between the INT and NOINT groups. Significance: Early periictal nursing intervention was associated with reduced duration of RD and reduced duration of PGES. These findings suggest the possibility that such interventions may be effective in reducing the risk of SUDEP in the outpatient setting. Validation of these preliminary data with a prospective study is needed before definitive conclusions can be reached regarding the efficacy of periictal interventions in reducing the risk of SUDEP.